Proline codon pair selection determines ribosome pausing strength and translation efficiency in bacteria - Ralph Krafczyk (Nature Portfolio, 2021)
Ralph Krafczyk et al. demonstrate that both proline codon usage and prolyl-tRNA abundance affect mRNA translation rates of polyproline-motifs in bacteria. These results provide additional insight into sequence-specific translation regulation.